TEACHERS’ PERCEPTION OF SEATING ARRANGEMENT ON STUDENTS' LEARNING CONCENTRATION - Rajni, Andi Febrianti; Muhayyang, Maemuna; Ariyani, Amra (Universitas Negeri Makassar, 2023)
The research aimed to determine the teacher's perception of the seating arrangement in student learning concentration. This research has subject were 3 english teacher who teach at SMPN 27 Makassar. This type of research is designed as qualitative descriptive research. The subjects were chosen by using a purposive technique. Data collected from interviews. The data obtained has been processed in several ways: data reduction, presentation, conclusion, and verification. Based on the result of the study, teachers' perceptions are divided into positive and negative perceptions. Positive perceptions include ease of application and the independent curriculum, helping understand the character and learning styles, the excellent and effective seating arrangement in learning English and understanding the ability to learn comprehension. Negative perceptions include a lack of learning concentration, limited capability to catch power, a lack of clear understanding of the material, and harmful influences that affect learning concentration. Based on the study's results, the teacher's perception equally dominates between positive and negative perceptions. Seating arrangements are, in fact, very influential on student learning concentration.